Enhancing [Spatial] Creativity - Alireza Mahdizadeh Hakak (A+BE: Architecture and the Built Environment)
Potentials of virtual environment for enhancing creativity of architects have shaped this research. There is no singular definition of creativity. In fact, there are more than 100 different definitions for creativity according to different contexts and disciplines. Nevertheless, it is possible to confine the boundaries of definitions and address creativity within a confined framework.